Structural Foams of Biobased Isosorbide-Containing Copolycarbonate - Stefan Zepnik; Daniel Sander; Stephan Kabasci; Christian Hopmann (International Journal of Polymer Science)
Isosorbide-containing copolycarbonate (Bio-PC) is a partly biobased alternative to conventional bisphenol A (BPA) based polycarbonate (PC). Conventional PC is widely used in polymer processing technologies including thermoplastic foaming such as foam injection molding. At present, no detailed data is available concerning the foam injection molding behavior and foam properties of Bio-PC. This contribution provides first results on injection-molded foams based on isosorbide-containing PC. The structural foams were produced by using an endothermic chemical blowing agent (CBA) masterbatch and the low pressure foam injection molding method. The influence of weight reduction and blowing agent concentration on general foam properties such as density, morphology, and mechanical properties was studied. The test specimens consist of a foam core in the center and compact symmetrical shell layers on the sides. The thickness of the foam core increases with increasing weight reduction irrespective of the CBA concentration. The specific (mechanical) bending properties are significantly improved and the specific tensile properties can almost be maintained while reducing the density of the injection-molded parts.